The effect of two types of iron-fortified formulas on the iron status of infants - Dimaano, Gemma P.; Bongga, Demetria C. (1985)
Iron-fortified proprietary formula has been used effectively in preventing iron deficiency anemia in the first year of life. The present study, conducted from September 1982 to Match 1983, was designed to determine the effect of cow's milk-based (casein-predominant) and soya-based (isolate) iron-fortified infant formulas on the iron status and growth of infants. The study involved 78 full term infants, 0-10 days old. They were fed for 90 days with either a cow's milk-based or soya-based formula. Weight and length measurements were taken every 30 days while hemoglobin and serum iron were determined at the beginning and end of the study. Formula consumption and nutrient intake were also analyzed to determine their relation to the iron status. Baseline examination indicated that blood hemoglobin and serum iron were similar for both groups. The subjects were also comparable in body weight, length, and gestation period. After 90 days, the group fed cow's milk-based formula showed significantly lower serum iron than the group fed soya-based formula. Further examination disclosed that the nature of protein and not the amount brought about the significant difference in serum iron between the 2 groups. However, the observed serum iron values were within the "acceptable" range. It was noted that the soya-fed group had significantly lower gain in body weight. However, the weight and length values fell within the normal percentiles for weight- and length-for-age. This indicated that the growth of the soya-fed group was just as good as the cow's milk formula group except that the infants in the soya group were leaner in comparison. Moreover, body weights of the two groups of infants was positively related to hemoglobin levels at 3 months.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Baby foods -- Iron content; Infant formulas; Infants -- Nutrition; Iron deficiency anemia in children; Iron